Transcriptomic and metabolomic profiling of strawberry during postharvest cooling and heat storage - Zheng, Ting; Lv, Jinhua; Sadeghnezhad, Ehsan; Cheng, Jianhui; Jia, Haifeng (Frontiers in Plant Science, 2022)
Temperature is one of the most important factors regarding fruit postharvest, however its effects in the strawberry fruits quality in postharvest remains to be evaluated. In this study, the effects of cold and heat storage temperature on fruit quality of ‘Benihoppe’ strawberry were performed. The results showed that different temperatures could affect the metabolism of hormone, anthocyanin, reactive oxygen species (ROS), and transcription level of responsive factors. The synthesis of terpenoids, amino acids, and phenylpropanoids in strawberries were also changed under different temperatures, which finally changed the quality characteristics of the fruit. We found HSF20 (YZ1)-overexpressed fruits were sensitive to cold and heat conditions but CBF/NF-Y (YZ9)-overexpressed fruits promoted coloring under cold treatment. This study clarified the effect of postharvest cooling and heat treatments on quality and transcriptional mechanism of strawberries fruits. Moreover, these results provided an experimental basis for further research on improving the quality of strawberry berries during postharvest periods.